Studies on Energy Consumption of Electric Light Commercial Vehicle Powered by In-Wheel Drive Modules - Piotr Szewczyk; Andrzej Łebkowski (Energies, 2021)
This article presents the results of energy consumption research for an electric light commercial vehicle (eLCV) powered by a centrally located motor (4 × 2 drive system) or motors placed in the vehicle’s wheels (4 × 4 drive system). For the considered constructions of electric drive systems, mathematical models of 4 × 2 and 4 × 4 drive systems were developed in the Modelica simulation environment, based on real data. Additionally, the influence of changes in the vehicle loading condition on the operation of the motor mounted in the wheel and the energy consumption of the drive module was investigated. On the basis of the conducted research, a comparative analysis of energy consumption by electric drive systems in 4 × 2 and 4 × 4 configurations was carried out for selected test cycles. The tests carried out with the Worldwide harmonized Light vehicles Test Cycles (WLTC) test cycle showed a roughly 6% lower energy consumption by the 4 × 4 drive system compared to the 4 × 2 configuration.